2010
DOI: 10.1111/j.1464-410x.2010.09203.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of tension‐free vaginal tape for treating stress incontinence in women with neuropathic bladders

Abstract: questionnaire (IIQ) forms (Urinary Distress Inventory, and IIQ-7) were assessed during the long-term clinical follow-up for SUI, in addition to a health-related quality of life assessment. The cure of SUI was defined as no loss of urine on physical exercise, confirmed VCMG after the procedure, and by clinical assessment. RESULTSThe mean (range) follow-up was 10 (8.5-12) years. Nine patients were using clean intermittent self-catheterization before the insertion of TVT and continued to do so afterward. At 10 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 10 publications
1
20
0
1
Order By: Relevance
“…Our results also compare favourably to previously reported success rates with tension-free vaginal tape, 4,5,15,16 with success rates at least as great with longer follow-up in our study. Furthermore, our results are comparable to those achieved in the general population undergoing TOT surgery.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results also compare favourably to previously reported success rates with tension-free vaginal tape, 4,5,15,16 with success rates at least as great with longer follow-up in our study. Furthermore, our results are comparable to those achieved in the general population undergoing TOT surgery.…”
Section: Discussionsupporting
confidence: 91%
“…4,5 This showed success comparable to non-neuropaths in both short and long term with few complications. The aim of this study was to present the first series of long-term safety and efficacy outcomes of placement of mid-urethral synthetic transobturator tapes (TOT) in patients with urodynamically confirmed SUI and NBD due to SCI.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…All four patients (two with SS-SCL and two with IS-SCL), previously treated with bulking agents, underwent the TVT procedure, when SUI occurred again after a second sphincter injection. 8,9 The only patient with IS-SCL who previously emptied her bladder spontaneously started AIC regimen after TVT surgery. A reduction of around 90% in SUI compared with baseline was maintained up to the final follow-up at around 6 years.…”
Section: Stress Urinary Incontinence Treatment: Bulking Agent Four Fmentioning
confidence: 99%
“…This result confirms previous positive findings in literature; therefore, TVT surgery should be part of the neuro-urologist's surgical armamentarium. 8,9 It was worth saying that at the time of patient inclusion in the studies, literature had not reported any data concerning, for example, the efficacy/safety of repetitive use of BoNT-A on SCL patients for NOB who were unresponsive to antimuscarinics or the use of SNM on subjects with SCL suffering from N-LUTD.…”
mentioning
confidence: 99%